Locating the frozen-unfrozen interface in soils using time-domain reflectometry - Baker, T. H. W.; Davis, J. L.; Hayhoe, H. N.; Topp, G. C. (1982)
The time-domain reflectometry technique was compared with the temperature measurement method for locating the frozen- unfrozen interface in water and sandy soils. This technique depends on the high-frequency (1-1000 MHz) electrical properties of water that change significantly and abruptly between the liquid and solid phases. Parallel wire transmission lines were inserted into the soil to guide electromagnetic pulses produced by a time-domain reflectometer (TDR). The frozen-unfrozen interface produced reflections measured by the TDR which were in turn used to locate the interface as it moved along the transmission line. In the laboratory it was possible to locate the interface using the TDR to within + or - 0.5 cm and in the field to within + or - 2.4 cm. These errors were equal to those associated with the temperature measurements. La technique de réflectométrie temps-domain a été comparée à la méthode de mesure de la température pour localiser l'interface glace-eau dans les sols sableux. Cette technique est fondée sur les propriétés électriques à haute fréquence (1-1000 MHz) de l'eau qui changent de facon abrupte et importante entre les phases liquide et solide. Des fils de transmission parallèles sont introduits dans le sol pour guider des impulsions électromagnétiques produites par un réflectomètre temps-domain (time-domain reflectometer, TDR). L'interface glace-eau produit des réflections mesurées par le TDR et qui sont utilisées pour situer l'interface lorsqu' il se déplace le long des fils de transmission. Il a été possible de situer l'interface au moyen de TDR avec une précision de + ou - 0,5 cm au laboratoire et de + ou - 2,4 cm sur le terrain. Ces erreurs sont égales à celles associées aux mesures de température. Peer reviewed: Yes NRC publication: Yes